FUNCTIONAL STUDY OF EFFLUX PUMP INHIBITORS IN CLINICAL ISOLATES OF MULTIDRUG RESISTANT KLEBSIELLA PNEUMONIAE - SURENDRANATH, C. R.; Ramana, B. V.; Chaudhury, Abhijit; Gururaj Kumar, A. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Recent studies showed that multidrug resistant (MDR) efflux mechanism is most common. The prevalence of active drug efflux pump was investigated in clinical isolates of Klebsiella pneumoniae (K. pneumoniae) exhibiting a multidrug-resistant phenotype in tertiary care hospital. Materials and Methods: The effects of efflux pumps inhibitors (EPI's) Reserpine 25 Âµg/ml and MC207-110 (Phe-Arg-beta-naphthylamide (PaÎ²N), Sigma) 25 Âµg/ml, was studied on MDR clinical isolates of K. pneumoniae. The MIC was performed for all the collected Clinical Isolates during the period of two years for fluoroquinolone in presence and in the absence of inhibitors as per the CLSI broth dilution method. Results: 10percent of the isolates have shown reduction in MIC in the presence of PaÎ²N and Reserpine. Conclusions: The study indicates the necessity for the detection of overexpressing efflux pumps at diagnostic level at least in tertiary care hospitals. Ketwords: EffluxsPump, K. pneumoniae, Reserpine, PaÎ²N, fluoroquinolone.